Victor Fleming : an American movie master - Sragow, Michael (The University Press of Kentucky, 2013)
Best remembered for bringing the iconic classics Gone with the Wind (1939) and The Wizard of Oz (1939) to the silver screen, Victor Fleming also counted successful films such as Red Dust (1932), Captains Courageous (1937), Test Pilot (1939), Dr. Jekyll and Mr. Hyde (1941), and the groundbreaking Joan of Arc (1948) among his more than forty directing credits. One of the most sought-after directors in Hollywood's golden age, Fleming (1889--1949) was renowned for his ability to make films across a wide range of genres. In this book, the author paints a portrait of the talented and charismatic man who helped create enduring screen personas for stars such as Clark Gable, Spencer Tracy, and Gary Cooper.